Ways to intensify innovation and import substitution in macrologistic systems of the Republic of Kazakhstan in the context of international integration - Kunyazov , E.K. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the current priorities for the development of macrologistic systems of the Republic of Kazakhstan that contribute to the development of innovation and import substitution in industry and the business sector. Particular attention is paid to the organizational and economic foundations of building macrologistic systems and their types, taking into account the vertical and horizontal integration of material and intangible flows, economic integration of the economies of near and far abroad countries. In the process of conducting the research, the current areas of production within the framework of the operation of vertical macrologistic systems in the Republic of Kazakhstan, taking into account the factors of international integration, are identified, the problems of macro-logistic that impede innovative development and import substitution in economic sectors are formulated. In order to solve logistics problems at the macro level, economic policy directions are proposed in two directions — with the participation of Kazakhstani enterprises and enterprises of near and far abroad, with the participation of the state. Practical recommendations have been developed for each direction, which predetermine the increasing role of macro-logistic systems in the innovative development of the economy, and the implementation of import-substitution business projects. The studies are applied in nature and can be widely used in practice in the framework of improving the industrial and innovative development policy of Kazakhstan, integrating the country into the global economy. The main research methods used were a systematic approach, analysis and synthesis, observation, and hypotheses.